The One Path the Four Foundations of Mindfulness - Thitaloko (Saeng Chan) , Phra Aeklak; Panasree, Sitthichok (Academic MCU Buriram Journal, 2025)
The reviewer has reviewed this book with the inspiration that it is an easy-to-read guide to meditation practice, easy for readers to understand, modern, and meets the needs of today's people who are quite busy and cannot go to meditation centers. The reviewer sees an interesting point in this book, which is the perspective of meditation practice of the new generation who are interested in meditation practice, which starts with creating correct understanding and has a guideline that can be truly practiced in life without having to go to meditation centers. However, readers can practice by themselves by worshiping Buddha, chanting, and meditating regularly in the morning and evening, and they will be able to be happy in life.